2014
DOI: 10.4103/0253-7176.127258
|View full text |Cite|
|
Sign up to set email alerts
|

Acute Antidepressant Effects of Intramuscular Versus Intravenous Ketamine

Abstract: Objective:Conventional antidepressants take two weeks before their therapeutic action begins. Recent studies have reported on the rapid antidepressant effect of ketamine when given as an intravenous (I.V.) infusion. Little is known about its intramuscular (I.M.) use in depression. Hence this study was conducted to compare the safety, tolerability and efficacy of I.M. versus. I.V. ketamine in Major Depression (ICD-10).Materials and Methods:It was a randomized open label parallel group study in a tertiary care t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 20 publications
5
66
0
3
Order By: Relevance
“…A follow-up case series in two Indian patients with depression also reported rapid antidepressant efficacy to intramuscular ketamine [Harihar et al 2013]. Finally, in a small (n = 9 in each group) randomized, open-label design, a separate Indian group reported antidepressant noninferiority (up to 3 days) with 0.25 mg/kg intramuscular ketamine compared with both 0.5 mg/kg intramuscular injection and 0.5 mg/kg intravenous infusion [Chilukuri et al 2014].…”
Section: Intramuscularmentioning
confidence: 91%
“…A follow-up case series in two Indian patients with depression also reported rapid antidepressant efficacy to intramuscular ketamine [Harihar et al 2013]. Finally, in a small (n = 9 in each group) randomized, open-label design, a separate Indian group reported antidepressant noninferiority (up to 3 days) with 0.25 mg/kg intramuscular ketamine compared with both 0.5 mg/kg intramuscular injection and 0.5 mg/kg intravenous infusion [Chilukuri et al 2014].…”
Section: Intramuscularmentioning
confidence: 91%
“…ketamine as a comparator. Chilukuri et al (2014) observed that 0.25 mg/kg IM ketamine produced the similar reductions in HAM-D to i.v. ketamine in MDD in an open label parallel group trial.…”
Section: Trials To Identify Mechanisms Of Ketamine Effectsmentioning
confidence: 68%
“…Additionally, Chilukuri et al (2014) randomized depressed patients to ketamine 0.5 mg/kg intravenously over 40 min versus 0.5 mg/kg or 0.25 mg/kg intramuscularly and found similar reductions in depression ratings at 2 h and 3 days post-dosing. However, there was no non-ketamine control group in that study.…”
Section: Ketamine For Depressionmentioning
confidence: 93%